Numerical analysis of fluid type and flow mass rate on logarithmic temperature difference and heat transfer coefficient of double pipe heat exchanger - EVRAN, SAVAŞ; KURT, MUSTAFA (My University, 2023)
This CFD and statistical article aims to evaluate the impact of fluid type and flow mass rate on the log-mean temperature difference (ΔTLM) and the heat transfer coefficient (Ushell) in a double tube heat exchanger (DPHEX) using computational fluid dynamics (CFD) and statistical analysis. ANSYS Fluent software was utilized to conduct CFD calculations. CFD analyses were implemented using Taguchi L8 orthogonal array containing two variables such as the fluid types and the flow mass rates. The levels of fluid types were considered as water-liquid, ethylene-glycol, engine-oil, and benzene-liquid. The levels of fluid types were decided as 1.1 kg/s to 1.5 kg/s. To determine the optimal levels of variables and their impacts on the ΔTLM and Ushell in DPHEX, analysis of Signal to Noise (S/N) ratio was employed. Analysis of Variance (ANOVA) was also utilized to decide the effective variables and their percentage contribution rates on the outcomes. The CFD result obtained using the optimum levels of variables were compared with Taguchi estimation result. According to the study, the highest effects were obtained using ethylene-glycol, engine-oil, water-liquid, and benzene-liquid on the highest log-mean temperature difference values, respectively. In addition, the highest heat transfer coefficient values were found utilizing water-liquid, benzene-liquid, ethylene-glycol, and engine-oil, respectively. Increasing flow mass rate from 1.1 kg/s to 1.5 kg/s causes an increase in both outcomes. The study provides a reference for resolving issues that may arise in the production of experimental DPHEXs.
Keywords: Matematik; Bilgisayar Bilimleri; Fizik; Yoğun Madde 1:Yapısal, Mekanik ve Termal Özellikler; Temel Bilimler; Mathematics; Computer Science; Physics; Condensed Matter 1: Structural, Mechanical and Thermal Properties; Natural Sciences; Temel Bilimler (SCI); MATEMATİK, UYGULAMALI; FİZİK, YOĞUN MADDE; Natural Sciences (SCI); MATHEMATICS; PHYSICS; MATHEMATICS, APPLIED; PHYSICS, CONDENSED MATTER; Sayısal analiz; Fizik Bilimleri; Yoğun Madde Fiziği; Numerical Analysis; Physical Sciences; Condensed Matter Physics; ANOVA; CFD; heat exchanger; Taguchi method; temperature; ANOVA; CFD; heat exchanger; Taguchi method; temperature